Edukasi Gosok Gigi untuk Meningkatkan Pengenalan Pola Hidup Bersih Sehat (PHBS) pada Anak Taman Kanak-Kanak Aisyiah Ranting 1 Kartasura Sukoharjo Jawa Tengah - Nurul Ilmi Azizah, Annafi; Fadhila, Nadia; Yulia Citra, Tamara; Ramadhani Lestari R, Nunik; Awalia, Wardati; Diyah Meilani, Rike; Cikal Rahmadanissa, Latifa; Agusta, Sukma (Mulya Literasi Publishing, 2024)
The introduction of a clean and healthy lifestyle through tooth brushing is expected to teach children how to brush their teeth correctly and regularly according to the procedure. Brushing teeth is a technique or process of cleaning dirt that can mechanically eliminate bad breath from the mouth using toothpaste and a toothbrush, followed by rinsing with clean water. Thus, the purpose of brushing teeth is a technique that children can perform for control and to prevent bacterial infections in the mouth, so that by brushing their teeth, they do not get cavities and remain white. This community service activity provides an introduction and practice on how to brush teeth to children at TK Aisyiah Ranting 1 Kartasura, which was held for one day on December 14, 2024, located in Dusun IV, Kartasura District, Sukoharjo Regency. The methods used are surveys, interviews, PHBS counseling, tooth brushing practice, and evaluation. The result of this PkM activity is that in addition to being able to brush their teeth correctly, the children can also apply a clean and healthy lifestyle in their daily lives